Pengembangan Kawasan Pabrik Gula di Kabupaten Takalar Development of the Sugar Factory Area in Takalar Regency - Jafar, Edy Efendy; Akbar, Andi Muhammad; Ikhsan, Andi Muhammad (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2026)
Sugar is a strategic commodity that plays a vital role in supporting consumption and industrial needs in Indonesia. However, national sugar production is currently unable to meet domestic demand, necessitating efforts to increase production capacity sustainably. One factory with the potential to contribute is the Takalar Sugar Factory (PG) in South Sulawesi, which has a steadily increasing supply of sugarcane as its raw material. The main problems faced by the Takalar Sugar Factory are the aging condition of its buildings and facilities, suboptimal spatial planning, and inadequate supporting infrastructure, which hinder optimal production. This study aims to formulate a concept for area development and improve the spatial planning of the Takalar Sugar Factory to meet industry standards and enable it to process all available raw materials. The research method used is descriptive-qualitative with a case study approach, through field observations, interviews, and documentation studies. The results show that area development with structured site management, clear zoning, and vertical building massing based on sugarcane identity can improve spatial efficiency, activity order, and the visual quality of the area. Thus, this re-planning is expected to increase production capacity, workforce productivity, and strengthen the role of the Takalar Sugar Factory in supporting national food security.